PENGARUH PENAMBAHAN TEPUNG KERABANG (CANGKANG TELUR) DALAM PROSES PENGOMPOSAN SAMPAH ORGANIK (SAMPAH RUMAH TANGGA) - isniati, Isniati (Lembaga Penelitian Universitas Negeri Padang, 2009)
The increasing of resident growth has contributed to the increasing of yielded garbage volume. The increasing of garbage volume has various problems concerned to the esthetics and health of contamination due to environment. To avoid the mentioned garbage, it is required to be managed better so that become a benefit to environmental human being. The composting process can be quickened by addition of eggshell. This research aims to know the rate of NPK compost with addition of eggshell and without addition of eggshell. This research was designed by pre test - post test to organic garbage like rest of vegetable, rest of foliage, and remains of fruits, ox dirt and eggshell. Data analyzed descriptively by comparing rate of NPK result of pengomposan with rate of NPK optimal compost. The result described the quality of compost with addition of eggshell got by percentage of Nitrogen rate 0, 6755, Phosphorus 49, 553%, and Calcium 0,767%. Percentage of compost with addition of ox dirt of N = 0, 7835 %, p = 0, 48706 %, K = 0, 88 % compost with addition of eggshell and ox dirt of N 0, 904%, P = 51, 682 %, K = 0, 941 result of analysis indicate that compost with addition of eggshell and higher ox dirt of percentage of rate of NPK its compared to addition of ox dirt and of eggshell. Organic garbage (rest of vegetable, rest of foliage, and remains of fruits) more efficient and be a benefit to human being and environment hence the organic garbage can be exploited standard upon which in making of compost. To quicken process of compost and improve the quality of compost can be used by eggshell. Keywords: composting process, organic garbage